Social Network Analysis shed light on a study case, a typical company with NodeXL - Kuz, Antonieta (2016)
The interest in social network has extended to different disciplines, such as Computer Science. This approach brings Social Network Analysis (SNA) as the study of social structure in different environments, like companies. For this reason, the present paper highlights basic network information like graphs using actors and relations, and important concepts related to companies like hierarchy. Finally, to obtain a practical approach of SNA, we describe the company as a sociometric experiment using NodeXL to verify the contrast of traditional Company chart and the application of sociometry to data sets; keeping attention to show how employees make informal contact and the knowledge this brings. Furthermore, companies in society, are a system of actors joined by relationships.